Scrolling Into Stagnation: A Qualitative Study on the Perceived Effects of ‘Brain Rot’ Among Students’ Communication Skills - Donaldo, Karen P. (PPSDP International Journal of Education, 2025)
This qualitative study investigates the perceived effects of the phenomenon colloquially known as “brain rot” on students’ communication skills. The term refers to the decline in cognitive and expressive functions resulting from prolonged exposure to passive digital content, particularly on social media platforms. Using semi-structured interviews with purposively selected students, this study sought to understand how excessive screen time influences verbal expression, social interaction, vocabulary development, and overall communication behaviour. Findings revealed recurring themes including reduced attention span, increased reliance on meme-based or short-form expressions, diminished face-to-face interaction confidence, and a perceived deterioration in critical thinking and vocabulary richness. While students acknowledged the benefits of digital connectivity, many reported feelings mentally fatigued and less articulate during offline conversations. These insights suggest that the overconsumption of fast-paced, visually stimulating content may gradually undermine fundamental communication abilities. The study concludes that “brain rot” is not merely a humorous online term but a reflection of a growing concern over digital media’s influence on essential life skills. It recommends the implementation of media literacy education, balance in screen time, and the reinforcement of traditional communication practices in educational settings.